PENERAPAN APLIKASI PENGELOLAAN BUMG DALAM MENINGKATKAN PAG DI GAMPONG LEUGE KABUPATEN ACEH TIMUR - Novianda; Rizalul Akram; Dewiyana (Fakultas Teknik, Universitas Samudra, 2025)
The Village-Owned Enterprise (BUMG) is an economic institution owned and managed by the village of Leuge. The purpose of this service is to improve the welfare of the village community by using the BUMG application to make work more efficient and effective. The methods used were the Pre-Activity Stage, which involved socialization; the Ongoing Activity Stage, which involved the implementation of the BUMG application; and the Post-Activity Stage. The results of the evaluation show that the percentage of application utilization, in terms of ease of data modification, increased from 76% to 87%, while the reporting system increased from 80% to 90%, and ease of application use increased significantly from 40% to 86%. Activities involving monitoring and guidance on the results of this activity include scientific publications in accredited national journals, online media publications, YouTube videos, and the skills and knowledge acquired by the community participating in PKM activities.